2003
DOI: 10.1023/b:plan.0000023671.99451.1d
|View full text |Cite
|
Sign up to set email alerts
|

L-Gulono-1,4-lactone oxidase expression rescues vitamin C-deficient Arabidopsis (vtc) mutants

Abstract: Vitamin C (L-ascorbic acid) has important antioxidant and metabolic functions in both plants and animals, humans have lost the ability to synthesize it. Fresh produce is the major source of vitamin C in the human diet yet only limited information is available concerning its route(s) of synthesis in plants. In contrast, the animal vitamin C biosynthetic pathway has been elucidated since the 1960s. Two biosynthetic pathways for vitamin C in plants are presently known. The D-mannose pathway appears to be predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…We predict that the identification of all the enzymes of the proposed D-Man/L-Gal pathway for ascorbate biosynthesis in plants (15) will soon be completed. This will provide a strong basis for understanding the control of ascorbate accumulation in plants and for investigating the contribution of pathways involving L-Gul (21) and uronic acid intermediates (49,51).…”
Section: Discussionmentioning
confidence: 99%
“…We predict that the identification of all the enzymes of the proposed D-Man/L-Gal pathway for ascorbate biosynthesis in plants (15) will soon be completed. This will provide a strong basis for understanding the control of ascorbate accumulation in plants and for investigating the contribution of pathways involving L-Gul (21) and uronic acid intermediates (49,51).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists that a minor pathway to ascorbic acid synthesis could proceed via myo-inositol synthesis (Baig et al, 1970;Radzio et al, 2003;Lorence et al, 2004;Torabinejad et al, 2009). We have previously shown that the vtc4 mutant (Conklin et al, 2006) has reduced myo-inositol and ascorbic acid levels, suggesting such a connection between these pathways (Torabinejad et al, 2009).…”
Section: Mips1 Impacts Inositol Synthesismentioning
confidence: 94%
“…Thus, in this context, a restoration of MI content in the absence of functional MIPS1 enzyme was surprising. However, evidence exists that a minor pathway to ascorbic acid synthesis could proceed via MI synthesis (Radzio et al, 2003;Lorence et al, 2004;Torabinejad et al, 2009). It has been previously shown that the vitamin c4 (vtc4) mutant, impaired in L-galactose-1-P phosphatase, a plant ascorbic acid biosynthetic enzyme (Conklin et al, 2006), has reduced MI levels, suggesting such a connection between these pathways (Torabinejad et al, 2009).…”
Section: Mips2 Is Responsible For MI Production In Mips1 Hxk1 Mutantsmentioning
confidence: 99%